Electronic Differential Network for LEV’s with two in-wheel motors (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper offers with layout, execution and evaluation of a digital differential machine meant for mild electric powered automobiles. Its performance is primarily supported on splitting the torque evenly for two unbiased brushless DC vehicles established within an identical axis of the automobile & immediately linked to both the wheel. This constellation lets in cars to revolve at one-of-a-kind velocities when the automobile follows a curve. The system finds as well as rectifies the skidding of any friction wheel/wheels.The principle characteristic of the projected device is that it doesn’t need a particular sensor to evaluate the guidance attitude and the velocity of the drive wheels. Every other crucial function is the miles applied exploiting widespread electric bicycle regulators and leading reason Arduino software. These additives are economical and to be had nearly everywhere in the world.